SDG10, Reduce inequality within and among countries - Pandey, Umesh Chandra; Kumar, Chhabi (Concise guides to the United Nations Sustainable Development Goals ;, 2020)
Defining inequality as the social, economic and political challenges of our time, this book will examine SDG10 to look ahead at how policy action might engage multiple stakeholders, involve diverse sectors and address gaps between policy and implementation to tackle key inequalities within and among countries.